Microscopic phase evolution mechanism of lithium slag and fiber synergistically enhancing concrete toughness: Perspective of preventing coal-rock dynamic disasters through energy absorption - Xuyang Bai; Junwen Zhang; Yulin Li; Zeyu Liu; Zhixiang Song; Yang Zhang; Xukai Dong; Shaokang Wu; Weizheng Xu; Xian Li (International Journal of Mining Science and Technology)
Coal and rock dynamic disasters are always major hidden dangers threatening mine safety production. Many researchers use cement concrete material as filling and energy-absorption materials. However, the current material toughness is not sufficient to meet the requirements of mine disaster prevention. Based on this, in order to find the optimal-ratio material that combines strength and toughness, the synergistic mechanism of lithium slag (LS), ethylene–vinyl acetate (EVA) copolymer, and polyvinyl alcohol (PVA) fiber mixtures in improving the mechanical properties of cement concrete, as well as the mechanism of microscopic phase evolution, was analyzed through macroscopic experiments, mesoscopic characterization, microscopic analysis, theoretical calculations, and comprehensive evaluation. The stress-strain curves obtained from the uniaxial compressive strength tests of specimens with different admixtures and fibers were investigated, and the characteristics of different stages were analyzed. The mechanical properties of different admixtures and fiber-reinforced materials, including their advantages and disadvantages, were compared through weighted comprehensive evaluation. The entire process of material failure, ranging from pore compaction, crack initiation, crack propagation, specimen instability to crack penetration, was explained via macroscopic fracture morphology, and the mechanical mechanism of how different admixtures affect the mechanical properties of concrete materials was revealed. The microscopic mechanism and the phase-evolution process of how the admixture affects concrete properties were elucidated using X-ray diffraction (XRD), hydration reaction theory, and Fourier transform infrared spectroscopy (FTIR). Furthermore, scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) was used to reveal the interfacial pore state and element distribution of the internal microstructure of concrete. The results show that PVA fiber bars can play the role of a “skeleton bridge” to improve the toughness of materials. LS can effectively promote the hydration process and cooperate with PVA fiber bars to enhance the mechanical properties of the material. EVA will inhibit the hydration reaction and degrade the material’s mechanical properties through the “organic isolation” effect. In addition, the on-site application has proven that the R3-group materials in this study can effectively inhibit the deformation of the roadway and possess strong reliability. Finally, the advantages and feasibility of LS-and-fiber-reinforced concrete were discussed from four perspectives: environmental protection, economy, disaster prevention, and development. This paper is expected to provide technical reference for the large-scale disposal of solid waste LS, the performance-optimization direction of concrete materials, and the prevention and control of coal and rock dynamic disasters.